Perubahan Adat Perkawinan Masyarakat Desa Kotadaro 1 Kecamatan Rantau Panjang Kabupaten Ogan Ilir 2010-2024 - Lestari, Anggun; R.Wargadalem, Farida (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines changes in marriage customs in Kotadaro 1 Village, Rantau Panjang District, Ogan Ilir Regency, between 2010 and 2024. This article examines changes in marriage customs in Kotadaro 1 Village, where many traditions have been abandoned by the local population over time, including marriage. The main objective of this study is to describe the changes in the marriage process in Kotadaro 1 Village and to explain the various meanings of the traditions contained within them as part of the endangered local wisdom. This study uses a historical method, commonly referred to as the historical method. The purpose of this historical research is to gain in-depth understanding of the events being studied, involving interviews, observation, and documentation studies. The methods used in historical research include a heuristic approach, source criticism, interpretation, and historiography. The results of this study demonstrate that changes in marriage customs have occurred in Kotadaro 1 Village. This change is due to increasingly modern developments. As a result, the traditional values contained within are threatened with extinction.